Maritime Asymmetric Warfare in Archipelagic States; The Indonesian Phenomena - Dwicahyono, Taufik; Octavian, Amarulla; Bura, Romie Oktavianus; Hendrantoro, Gamantyo; Widodo, Pujo (UI Scholars Hub, 2021)
Defending sovereignty within an island nation is relatively more complex than doing so for a continental state. The number of scattered islands makes straits and seas more penetrable, vulnerable points and targets of asymmetric threats at sea. The aim of this research is to illustrate threats at sea and provide solutions in guarding and monitoring Indonesian coastal borders, which currently require more ships and radar technology as well as other sensing equipment due to longer beaches. The results reveal that firstly, potential asymmetrical threats at sea include former WWII mines, underwater fibre cables, and nuclear submarines belonging to foreign countries such as America, Russia and China. Secondly, problems related to welfare include theft of natural resources like coral reefs and fish, and drug smuggling activities, all which add to the burden and duties of various parties. Thirdly, asymmetrical Narcoterrorism is very prominent in Colombia where drugs from Cannabis plants are sold to buy weapons. This is also happening in the Philippines and in Aceh, Indonesia. Narcotic activities are also increasingly worrying – particularly their effects on younger generations. Lastly, coordination by affiliated parties that help guard the sea is highly expected. Adequate maritime border patrol management must be carried out so that together, different marine security institutions can maintain the sovereignty of the state. Therefore, the following are recommended: a) regional diplomatic cooperation within ASEAN, b) ensuring of military capability, power, and readiness for placement, and c) the utilization of unmanned technology to aid in securing the archipelagic state.